2005
DOI: 10.1111/j.0014-3820.2005.tb01012.x
|View full text |Cite
|
Sign up to set email alerts
|

EXPERIMENTAL STUDIES OF ADAPTATION IN clarkia xantiana:II. FITNESS VARIATION ACROSS A SUBSPECIES BORDER

Abstract: Abstract. Because the range boundary is the locale beyond which a taxon fails to persist, it provides a unique opportunity for studying the limits on adaptive evolution. Adaptive constraints on range expansion are perplexing in view of widespread ecotypic differentiation by habitat and region within a species' range (regional adaptation) and rapid evolutionary response to novel environments. In this study of two parapatric subspecies, Clarkia xantiana ssp. xantiana and C. x. ssp. parviflora, we compared the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…replacement) at both sites in the beyond edge region, the 95% confidence intervals of seed production included values below one (not shown), indicating that even these populations, though best-adapted to this region, may not maintain themselves here based on data from this year of study. This is consistent with other studies that find adaptation of populations to conditions at the range edge, though absolute fitness below that necessary to sustain the populations when transplanted beyond the range edge [38], [39]. By contrast, other studies have not found a reduction in fitness beyond the range edge [40]–[42].…”
Section: Discussionsupporting
confidence: 92%
“…replacement) at both sites in the beyond edge region, the 95% confidence intervals of seed production included values below one (not shown), indicating that even these populations, though best-adapted to this region, may not maintain themselves here based on data from this year of study. This is consistent with other studies that find adaptation of populations to conditions at the range edge, though absolute fitness below that necessary to sustain the populations when transplanted beyond the range edge [38], [39]. By contrast, other studies have not found a reduction in fitness beyond the range edge [40]–[42].…”
Section: Discussionsupporting
confidence: 92%
“…This proposed route to FT divergence is an example of countergradient selection leading to genetic compensation, wherein selection in the opposite direction of a plastic response leads to genetic change decreasing the amount of plasticity [21]. Countergradient selection in FT has been documented in other annual plants [59,60], including a study of ecotypes on and off of edaphically harsh mine tailings in Thalspi caerulescens [61].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the studies available for that meta-analysis likely did not assess variation in fitness at very early life history stages. Indeed, few reciprocal transplant studies have investigated the seed to seedling transition; therefore, we lack a comprehensive understanding of local adaptation in germination success (Donohue et al 2010; Geber and Eckhart 2005; Kim and Donohue 2013; Wilczek et al 2014). Germination is a critical life history transition, as seeds that fail to germinate have no future fecundity.…”
Section: Discussionmentioning
confidence: 99%